Modeling Economic Growth: Domar on Moving Equilibrium - Mauro Boianovsky (Duke University, Center for the History of Political Economy (CHOPE), 2015)
The paper investigates Evsey's Domar's introduction of the rate of growth as a variable in economics in the 1940s and 1950s . Domar investigated the nature of what he called the "moving equilibrium" of ec onomic processes with infinite duration. Reactions to Domar' s approach at the time brought about methodological assertions on the distinction between models and theories. Domar's model was an open one, in the sense that his growth equation allowed different closures. A main feature of the model was its relatively stable capital - output ratio, whi ch reflected the terms of the debate about A.H. Hansen's stagnation thesis in the 1940s and the notion of limits to capital deepening. At the empirical level, Domar referred to some features of time series, such as the positive trend of output per capita. Differently from Harrod, t he real economy was supposed to be stable, although the model itself was not perfectly consistent with that. The estimation of the Residual (a term coined by Domar) by Solow and others led Domar to rethin k aspec ts of his original model
Keywords: B21; C6; C92; B4; D03; D61; G28; 330; Domar; growth economics; models; capital - output ratio; stability